ANALISIS GAYA BELAJAR SISWA SDN 060/IXMUARO JAMBI MENGGUNAKAN FUZZY C-MEANS (FCM): Auditory, Fuzzy C-Means, Kinesthetic, Learning Style, Visual - Fitri Yusni, Vuspa; Puspitorini, Sukma; Lisdarti, Lisdarti (FORTECH (Journal of Information Technology), 2025)
Learning styles are an essential factor influencing the effectiveness of the learning process. Each student has different tendencies, such as visual, auditory, or kinesthetic. This study aims to analyze the learning styles of elementary school students using the Fuzzy C-Means (FCM) method. The data consisted of report card scores from nine subjects, representing academic achievement, and a learning style questionnaire. The questionnaire results indicated that 19 students (43.18%) preferred visual learning, 6 students (13.64%) auditory, 10 students (22.73%) kinesthetic, and 9 students (20.45%) had mixed learning styles. FCM was chosen because it allows clustering with multiple memberships, enabling students to belong to more than one learning style category. A total of 44 students’ data were processed using MATLAB and Microsoft Excel. The clustering results identified three main clusters: visual (C1) with 18 students (40.91%), auditory (C2) with 12 students (27.27%), and kinesthetic (C3) with 14 students (31.82%). These findings provide useful insights for teachers to design more effective teaching strategies tailored to students’ learning styles.